Long-term maintenance of pediatric asthma: focus on budesonide/formoterol inhalation aerosol - Peter N Huynh; Lyne G Scott; Kenny YC Kwong (Dove Medical Press, 2010)
Peter N Huynh1, Lyne G Scott1, Kenny YC Kwong21Division of Allergy-Immunology, Department of Pediatrics, Los Angeles County, University of Southern California Medical Center, Los Angeles, CA, USA; 2Division of Allergy-Immunology, Department of Pediatrics, Harbor-UCLA Medical Center, Torrance, CA, USAAbstract: Current national and international asthma guidelines recommend treatment of children with asthma towards achieving and maintaining asthma control. These guidelines provide more stringent recommendations to increase therapy for patients with uncontrolled asthma in order to reduce asthma-related morbidity and mortality. Newer combination agents such as budesonide and formoterol have been shown to be safe and effective in treatment of asthma in children. Use of long-term controller agents like this in combination with improved compliance and treatment of co-morbid conditions have been successful in this endeavor. This review discusses control of pediatric asthma with focus on the use of budesonide in combination with formoterol.Keywords: asthma, control, children, budesonide, formoterol, long-term